Women in aquaculture: a case study in the Marajó archipelago, Brazil (Research, Society and Development, 2020)
The participation of women in different areas of society is important for human reproduction and the development of various economic, social and cultural activities. The objective of this study was to reflect on woman participation in aquaculture in the Marajó archipelago (Pará - Brazil). The study was based on reports from five women who practice fish farming in the municipality of Curralinho, in March 2020. This methodology was the result of an extension project “Transfer of technology through training and technical assistance for fish farmers of tambaqui, Colossoma macropomum, in the archipelago of Marajó/PA”, from the Federal Institute of Education, Science and Technology of Pará (IFPA) Campus Breves. We observed that the creation of tambaqui in the region is also practiced by women, for subsistence. They have approximately 2 years of experience with fish farming. Most aquaculture companies are between 18 and 66 years old, have 2 to 4 children, with elementary education and are not part of any social organization. The training course on Good Management Practices in Fish Farming (BPM) aimed at strengthening the activity for the female group. In conclusion, women are protagonists of their own history and are present in the aquaculture universe, being important figures in the productive context in Marajó, Eastern Amazon.